Generalized verrucosis and abnormal T cell activation due to homozygous TAOK2 mutation. Issue 2 (August 2017) - Molho-Pessach, Vered; Ramot, Yuval; Mogilevsky, Maxim; Cohen-Daniel, Leonor; Eisenstein, Eli M.; Abu-Libdeh, Abdulsalam; Siam, Ihab; Berger, Michael; Karni, Rotem; Zlotogorski, Abraham
Highlights: A homozygous mutation in TAOK2 causes a novel form of primary immunodeficiency. Generalized verrucosis and recurrent infections are clinical features of this condition. Inflammatory bowel disease may be associated. T cell proliferation upon activation is impaired. Abstract: Background: Generalized verrucosis (GV) is a chronic and progressive cutaneous human papillomavirus (HPV) infection resulting in multiple warts and associated with acquired or genetic immune defects. We identified a consanguineous Arab family manifesting GV and recurrent bacterial and viral infections, in association with inflammatory bowel disease (IBD). Objective: To identify the mutated gene responsible for GV, recurrent infections and IBD, in this family. Methods: Flow cytometry of peripheral blood mononuclear cells was performed, as well as proliferation and cell cycle assays of T cells. Whole exome sequencing was utilized to detect candidate mutated genes, assuming an autosomal recessive mode of inheritance. Skin fibroblasts from a patient, the mother and control were incubated with sorbitol to detect the phosphorylation ability of TAOK2, and a clonogenic assay was performed to assess the survival and proliferative capacity of fibroblasts' colonies. Results: Despite normal immunophenotyping of T and B cells, T cell proliferation upon activation was impaired in a patient compared to a heterozygous family member and a control. Genetic analyses identified a rare homozygous missense variant, c.2098C>T (p.R700C) in the TAOK2 gene, segregating with the disease phenotype in the family. TAOK2 encodes the TAO2 kinase, a mitogen activated protein kinase kinase kinase (MAP3K) in the p38-MAPK cascade. The mutation is predicted to disrupt its normal folding and molecular interaction; however, no impairment was observed in TAOK2 kinase activity toward its downstream target, MEK3/6, in patient's fibroblasts. Despite this normal kinase activity, a noticeably higher survival/proliferation of patient's skin fibroblasts was found. Conclusions: A mutation in TAOK2 appears to cause a novel form of primary immunodeficiency, characterized by an impaired T cell proliferation upon activation. This novel cause of GV gives further support to the importance of the p38-MAPK pathway in the immune response against HPV, and possibly also in the pathogenesis of IBD.